The validity of the Push Band 2.0 to determine speed and power during progressively loaded squat jumps - Orser, K.; Agar-Newman, D. J.; Tsai, M.; Klimstra, M. (Sports Biomechanics, 2024)
The PUSH band 2.0 is a wearable technology used to measure mean and peak velocity and power in strength-based movements. The agreement between the PUSH band 2.0 and the criterion measure (force plates) during progressively loaded squat jumps was assessed. Fifteen participants performed 3 squat jumps at increasing loads. Linear regression and Bland-Altman plots assessed data simultaneously recorded from both devices. Mean velocity and power showed deviation from the identity line and an overestimation of 7.40% and 25%, respectively. Peak velocity and power showed an overestimation of 14% and underestimation of 6%, respectively. The results support the use of Push Band 2.0 to measure velocity during ballistic squat movements. However, errors in power measurement are greater than acceptable to support in-field use. While peak velocity maintains a consistent overestimation bias across various velocities, mean velocity error increases at higher velocities and can only be considered valid at slow velocities.